Effect of Banana Peels Extract Ratio on The Sustainable Eco-Friendly Synthesis of Zinc Oxide Nanoparticles - Alwash, Atheel; Ibrahim, Farah M.; Mohammed, Salam (Al-Nahrain Journal for Engineering Sciences, 2023)
In this work, environmentally friendly zinc oxide nanoparticles was produced using sustainable green technology. With several loading amounts, such as 5%, 10%, 50%, and 100%, the banana peel extract was utilized as a capping agent. This was followed by calcinations at 400 ºC for 3 h in a muffle furnace. To evaluate the physical and chemical change of the synthesized nanoparticles, XRD, FTIR, UV-VIS and SEM/EDAX was used. The characterization results reveald that the all the green synthesized ZnO NPs samples strongly supports the well-crystallinity with high phase purity. The average crystallite size of the prepared samples was calculated using Debye-Scherer's formula and the results shows that with an increase in extract amount, the average crystallite size was shrinking. The FTIR result verified the successful chemical reaction between zinc salt and banana peel extract. The UV-VIS results showed the effect of size quantisization phenomena at 100% extract adding. Finally, the SEM images for all the prepared samples confirm the spherical shape.